Trade liberalization, environment and poverty: A developing country perspective - M. S. Qureshi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper revisits the pollution haven hypothesis in the context of Pakistan by offering a systematic analysis of its trade and production patterns. Using bilateral trade statistics from 1975-2003, we test the hypotheses that Pakistan's net exports of pollutionintensive products have increased to the OECD countries. We also investigate if the stringency of environmental governance in the importing countries plays a role in determining Pakistan's exports of pollution-intensive products. The results reveal that there has been a change in the composition of output and exports towards pollutionintensive manufacturing that parallels the opening of the economy. Overall, the findings appear to be in favour of the pollution haven hypothesis and call for effective environmental policy response for poverty alleviation and sustainable development.
Keywords: F18; O13; L60; Q56; 330; international trade; industrial pollution; composition effect; gravity model; Pakistan; Industrielle Umweltbelastung; Außenhandelsliberalisierung; Außenhandelsstruktur; Pakistan